Bridging Science and Vocational Skills: An Analysis of Kurikulum Merdeka Implementation in Islamic High Schools - Roy Ekanala (Jurnal Penelitian Pendidikan IPA, 2026)
This study analyzes the implementation of Kurikulum Merdeka in bridging science education and vocational skill development at an Indonesian Islamic high school. Utilizing a qualitative case study approach, the research examines how project-based learning integrates theoretical scientific concepts with practical vocational applications. The principal results reveal that interdisciplinary projects, such as transforming used cooking oil into aromatic candles and producing natural-dye batik, successfully translate chemical principles into market-oriented entrepreneurial competencies. This integration significantly enhances student creativity, cultural appreciation, and collaborative problem-solving. However, the implementation faces notable challenges, including limited teacher readiness for interdisciplinary pedagogical design, project time management issues, and resource constraints. The study concludes that while the curriculum effectively dismantles the traditional academic-vocational dichotomy, its sustained success depends on targeted professional development for teachers, robust institutional scaffolding for project governance, and strategic resource allocation. These findings provide actionable insights for optimizing competency-based education in faith-based institutions.